2014
DOI: 10.3390/nu6051861
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12-Containing Plant Food Sources for Vegetarians

Abstract: The usual dietary sources of Vitamin B12 are animal-derived foods, although a few plant-based foods contain substantial amounts of Vitamin B12. To prevent Vitamin B12 deficiency in high-risk populations such as vegetarians, it is necessary to identify plant-derived foods that contain high levels of Vitamin B12. A survey of naturally occurring plant-derived food sources with high Vitamin B12 contents suggested that dried purple laver (nori) is the most suitable Vitamin B12 source presently available for vegetar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
131
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(140 citation statements)
references
References 66 publications
2
131
0
7
Order By: Relevance
“…Dried green and purple laver have been the most popular selections of edible seaweed and also contain high amounts of vitamin B 12 . [33,34] Vitamin B 12 is most commonly found in animal sources and therefore are more difficult to obtain with lower meat consumption. [33] Surveys conducted by NHANES indicated a peak in meat consumption from ages 20-49 and a decrease in meat consumption in older age.…”
Section: World Journal Of Pharmacy and Pharmaceutical Sciencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dried green and purple laver have been the most popular selections of edible seaweed and also contain high amounts of vitamin B 12 . [33,34] Vitamin B 12 is most commonly found in animal sources and therefore are more difficult to obtain with lower meat consumption. [33] Surveys conducted by NHANES indicated a peak in meat consumption from ages 20-49 and a decrease in meat consumption in older age.…”
Section: World Journal Of Pharmacy and Pharmaceutical Sciencesmentioning
confidence: 99%
“…[33,34] Vitamin B 12 is most commonly found in animal sources and therefore are more difficult to obtain with lower meat consumption. [33] Surveys conducted by NHANES indicated a peak in meat consumption from ages 20-49 and a decrease in meat consumption in older age. [35] The decrease in meat consumption may create deficiencies in vitamin B 12 and other nutrients that may be risk factors to depression and dementia.…”
Section: World Journal Of Pharmacy and Pharmaceutical Sciencesmentioning
confidence: 99%
“…Some authors disagree with this fact [9,10], but recent studies have shown that plant cell has the ability to produce only similar to B12 compounds (called pseudo-B12), which compete with B12 for the same cellular receptors, i.e., prevent normal physiological absorption of B12 [11].…”
Section: Introductionmentioning
confidence: 99%
“…8 Thus, strict vegetarians and elderly people have an increased risk of developing B 12 deficiency. 6,9 Megaloblastic anemia and neuropathy are wellknown symptoms of B 12 deficiency, 6 but the molecular mechanism underlying such diseases is still poorly understood. 10 Caenorhabditis elegans, consisting of 959 somatic cells, shows a very short life cycle and has the ability to change its locomotor behavior, reproductive rate, and lifespan.…”
Section: Introductionmentioning
confidence: 99%